Improving Overall Survival and Quality of Life in Patients with Prostate Cancer and Neuroendocrine Tumors Using 177Lu-iPSMA and 177Lu-DOTATOC: Experience after 905 Treatment Doses - Myrna Luna-Gutiérrez; Rodrigo Hernández-Ramírez; Airam Soto-Abundiz; Osvaldo García-Pérez; Alejandra Ancira-Cortez; Sergio López-Buenrostro; Brenda Gibbens-Bandala; Irma Soldevilla-Gallardo; Nancy Lara-Almazán; Melissa Rojas-Pérez; Blanca Ocampo-García; Erika Azorín-Vega; et al. (MDPI AG, 2023)
177Lu-iPSMA is a novel radioligand developed at ININ-Mexico with a high affinity for the PSMA protein heavily expressed in cancer cells of approximately 95% of patients with metastatic castration-resistant prostate cancer (mCRPC). 177Lu-DOTATOC is a patent-free radioligand, molecularly recognized by somatostatin receptors (SSTR-2) overexpressed in cancer cells of about 80% of patients with metastatic gastroenteropancreatic neuroendocrine tumors (GEP-NET). This translational research aimed to determine the efficacy and safety of 177Lu-iPSMA and 177Lu-DOTATOC developed as GMP pharmaceutical formulations for treating progressive and advanced mCRPC and NET. One hundred and forty-five patients with mCRPC and one hundred and eighty-seven subjects with progressive NET (83% GEP-NET and 17% other NET), treated with 177Lu-iPSMA and 177Lu-DOTATOC, respectively, were evaluated. Patients received a mean dose of 7.4 GBq per administration of 177Lu-iPSMA (range 1-5 administrations; 394 treatment doses) or 177Lu-DOTATOC (range 2-8 administrations; 511 treatment doses) at intervals of 1.5-2.5 months. Efficacy was assessed by SPECT/CT or PET/CT. Results were stratified by primary tumor origin and number of doses administered. Patients with mCRPC showed overall survival (OS) of 21.7 months with decreased radiotracer tumor uptake (SUV) and PSA level in 80% and 73% of patients, respectively. In addition, a significant reduction in pain (numerical scale from 10-7 to 3-1) was observed in 88% of patients with bone metastases between one and two weeks after the second injection. In the GEP-NET population, the median progression-free survival was 34.7 months, with an OS of >44.2 months. The treatments were well tolerated. Only ten patients experienced grade ≥ 3 myelosuppression (3% of all patients). The observed safety profiles and favorable therapeutic responses demonstrated the potential of 177Lu-iPSMA and 177Lu-DOTATOC to improve overall survival and quality of life in patients with progressive and advanced mCRPC and NET.